Cumulative additional information does not improve the neuromuscular control during postural responses to perturbations in postural instability/gait disorders subtype of Parkinson's disease - Beretta, Victor Spiandor [UNESP]; Santos, Paulo Cezar Rocha [UNESP]; Orcioli-Silva, Diego [UNESP]; Jaimes, Diego Alejandro Rojas [UNESP]; Pereira, Marcelo Pinto [UNESP]; Barbieri, Fabio Augusto [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2022)
Background: Postural response impairments in postural instability and gait disorders (PIGD) subtype patients may be attributed to Parkinson's disease (PD)-deterioration in central-set (programing/modulating of central outputs during motor responses). Although additional information improves some PD motor impairments, an unanswered question is whether additional information can benefit postural response in PIGD subtype. Objective: To analyze the effect of cumulative additional information on postural responses after perturbation in PIGD and neurologically healthy older adults (CG). Methods: Perturbations were applied in 16 PIGD and 19 CG by the support-base translation. Participants performed 3 blocks of 5 trials without additional information (B1–B3, Day 1) and 5 trials of each cumulative additional information (C1–C4, Day 2): information about perturbation (C1), visual (C2), verbal (C3), and somatosensory information (C4). Electromyography and center of pressure (CoP) parameters were analyzed by ANOVAs with Group (PIGD × CG) and Block (B1 × B2 × B3) and with Group (PIGD × CG) and Condition (B3 × C1 × C2 × C3 × C4). Results: PIGD decreased the range of CoP in B3 while CG decreased both range of CoP and the integral of antagonist's muscle activity (iEMG) in B2. Also, PIGD decreased the recovery time in C4 while CG increased the iEMG of agonist's muscle in C2 and antagonist's muscle in all conditions except C2. Conclusion: Additional information provided before postural control assessment influences the postural response in PIGD and CG differently. PIGD demonstrated inflexibility of central-set in modulating the neuromuscular control regardless of additional information. CG presents a flexible system evidenced by the increase of agonist muscle iEMG when provided visual information.
Keywords: Cues; Habituation; Movement disorders; Neurodegenerative diseases; Postural balance